Security cooperation in the Baltic Sea region: Today and future in the world context - Makštutis, Antanas (Journal of Business Economics and Management, 2005)
The paper analyzes the global economic factors of security cooperation in the Baltic Sea region that have an effect on the present and future development of national markets in separate states of this region within the development of the common market of the European Union (EU). It is noted that the EU principal market factors of today: the free movement of people, goods and capital destabilizes the development of a separate state market in the Baltic Sea region, and the tasks of a national state in the future will become still more complicated. The work provides the research results of the factors of a specific geopolitical environment in the Baltic Sea region; the ways and methods are foreseen for solving the future political, economic and social problems in this region under the conditions of globalization.First Published Online: 14 Oct 2010